Measurement of Bs0 Mixing Parameters from the Flavor-Tagged Decay Bs0→J/ψ - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
From an analysis of the flavor-tagged decay Bs0→J/ψ we obtain the width difference between the Bs0 light and heavy mass eigenstates, ΔΓs=0.19±0.07(stat)-0.01+0.02(syst)ps-1, and the CP-violating phase, s=-0.57-0.30+0.24(stat)-0.02+0.08(syst). The allowed 90% CL intervals of ΔΓs and s are 0.06<ΔΓs<0.30ps-1 and -1.20